Analysis of Risk Factors Affecting the Development of Infection in - Koc, C; Akbulut, S; Ozdemir, F; Kose, A; Isik, B; Yologlu, S; Yilmaz, S (2019)
Background. To analyze the risk factors affecting the development of infection in artificial vascular grafts (AVGs) used for reconstruction of middle hepatic vein (MHV) tributaries in living donor liver transplantation (LDLT). Methods. Between January 2009 and January 2018, 1253 right lobe LDLTs were performed at our Transplant Institute, and MHV tributaries of the 640 right lobe liver grafts were reconstructed with AVG. Reconstructed MHV tributaries were removed due to AVG infection in 25 of these patients (case group; n = 25). To determine risk factors for AVG infection, right lobe LDLT patients without AVG infections were selected as control group (n = 615). Both groups were compared about demographic parameter, transcystic catheter usage, bile leakage, type of biliary anastomosis (duct-to-duct, telescopic duct-to-duct), number of graft biliary duct (=1 versus >1), number of biliary anastomosis (=1 versus >1), AVG thrombosis, AVG types (Dacron versus polytetrafluoroethylene). Univariate analyses were used for comparison of different variables, and variables with P <= 0.20 were taken into logistic regression model. Results. Univariate analysis shows that statistically significant differences were found between groups regarding bile leakage (P < 0.001), graft thrombosis (P = 0.002), transcystic catheter (P = 0.049), and AVG types (P = 0.013). Variables with P <= 0.20 were taken into logistic regression model. Multivariate analysis shows that bile leakage (odds ratio, 13.3) and AVG thrombosis (odds ratio, 9.8) were determined as independent and strong risk factors for development of AVG infection. Conclusions. This study revealed that bile leakage and graft thrombosis are independent and strong risk factors for infections of AVGs used for anterior sector drainage reconstruction. C1 [Koc, Cemalettin; Akbulut, Sami; Ozdemir, Fatih; Isik, Burak; Yilmaz, Sezai] Inonu Univ, Dept Surg, Fac Med, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. [Koc, Cemalettin; Akbulut, Sami; Ozdemir, Fatih; Isik, Burak; Yilmaz, Sezai] Inonu Univ, Liver Transplant Inst, Fac Med, Elazig Yolu 10 Km, TR-44280 Malatya, Turkey. [Kose, Adem] Inonu Univ, Dept Infect Dis & Clin Microbiol, Fac Med, Malatya, Turkey. [Yologlu, Saim] Inonu Univ, Dept Biostat, Fac Med, Malatya, Turkey.